The Effects of Concept Cartoons on Eliminating Students' Misconceptions: Greenhouse Effect and Global Warming - Lale Cerrah Ozsevgeç; Arzu Erdoğan (Mehmet Tekerek, 2012)
The aim of the study is to examine the effects of concept cartoons on eliminating students' misconceptions about the global warming and greenhouse effect. The sample of the study is consisted of 17 students from the 7 grade of Rize Çay Primary School. Simple experimental study design was used in the study. Test and semi-structured interview were used to collect the data. The results of the study showed that the students had misconceptions about global warming and greenhouse effect. The teaching process comprising concept cartoons treated most of these misconceptions. Students indicated that the teaching process was enjoyable and it eased the students' remembering of the given knowledge. Based on the results, it was suggested that the teachers should be informed about the usage of concept cartoon in the classroom and combination of different teaching methods which is supported by concept cartoon may be more useful for different science subjects.